KONVERGENSI DAN DIVERGENSI PENANGANAN KESEHATAN MASYARAKAT TERKAIT KEGAWATDARURATAN AKIBAT BENCANA - Ningsih, Endang Suprihati; Adawiyah, Rabiatul; Heriyadi, Muhammad; Putri, Keina Salsabila Ilmi (Politeknik Unggulan Kalimantan, 2025)
There has been an increase in the number of floods and victims affected. This incident has caused health problems for the community in Banjarmasin. Emergency response in the field is still hampered by the information system. This study is limited to the city of Banjarmasin, but it can describe South Kalimantan Province because the mechanisms are the same. Referring to the concepts of convergence and divergence, this study was conducted using interpretive phenomenology. It was analyzed using the I.P.A. principle, assisted by NVIVO software to facilitate visualization. The results of the study show that, in terms of structural convergence, the Banjarmasin health cluster implements a top-down mechanism that is still in use. In terms of operational convergence, although the Health Office has an SKDR information system, the process still relies heavily on manual systems. Operations only rely on WhatsApp groups, and the reporting of disaster victim and patient data is still manual. This causes divergence in the field, which is prone to data and personnel errors. It is hoped that in the future there will be an integrated one-stop information system that can be utilized by health clusters both specifically and generally in Indonesia.